An investigation of teachers' and teaching assistants' causal attributions for challenging behaviour in primary school settings - Raspin, Sarah (2019)
The negative impact of challenging behaviour within the primary school classroom is widely acknowledged, with research indicating that the attributions held by school staff can affect their approach to behaviour management, as well as their overall motivation and confidence in supporting challenging behaviour. The present study aimed to explore the causal attributions made by school staff for challenging behaviour observed in pupils aged 4-11.